2010
DOI: 10.1080/09540121003668110
|View full text |Cite
|
Sign up to set email alerts
|

Coping and psychological adjustment in adolescents with vertically acquired HIV

Abstract: Children with vertically acquired HIV face the challenges of adolescence in addition to the demands of coping with their illness. The relationship between coping and psychological adjustment has been widely studied in adults and children with chronic diseases but it is poorly understood in adolescents with HIV. This study aimed to identify whether a UK sample of adolescents with vertically acquired HIV had poor psychological adjustment and to clarify the relationship between coping and psychological adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Data from the French CO10 cohort showed that school performance was comparable to national statistics [79]. However, Swiss and UK studies have illustrated that coping with HIV was an ongoing challenge for PHIVA as they became older, and that inconsistent disclosure and poor psychological adjustment had a negative impact on long-term adherence [80, 81]. As mentioned above, a very important issue that needs to be addressed is how to continue to follow these youth as they transition to adult care, especially given that a number of the findings to date regarding hyperlipidemia, bone density, and the impact of mental health and other central nervous system disorders may not be fully expressed until later in adulthood.…”
Section: Europementioning
confidence: 99%
“…Data from the French CO10 cohort showed that school performance was comparable to national statistics [79]. However, Swiss and UK studies have illustrated that coping with HIV was an ongoing challenge for PHIVA as they became older, and that inconsistent disclosure and poor psychological adjustment had a negative impact on long-term adherence [80, 81]. As mentioned above, a very important issue that needs to be addressed is how to continue to follow these youth as they transition to adult care, especially given that a number of the findings to date regarding hyperlipidemia, bone density, and the impact of mental health and other central nervous system disorders may not be fully expressed until later in adulthood.…”
Section: Europementioning
confidence: 99%
“…Furthermore, many studies to date have utilized cross-sectional designs and cannot adequately assess the impact of disclosure on clinical or psychosocial characteristics [6]. Other studies suggest that HIV-infected children who know their status may be better able to seek social support, have improved coping skills [11,22] and practice safer sexual practices to prevent secondary transmission [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Only three studies on HIV‐infected children assessed the prevalence of psychological distress with respect to a comparison sample. In two (Moss, Bose, Wolters, & Brouwers, 1998; Sopena, Evangeli, Dodge, & Melvin, 2010), levels of mental health problems and resilience among HIV‐infected children were compared with published national norms in the U.S. and U.K. (respectively); no significant differences were found in either case. The third study (conducted in the U.S.) used a control/comparison design to assess adaptive outcomes and levels of emotional and behavioral problems among 403 children and adolescents (age 6–19 at study initiation) at varying stages of disease progression (four groups based on CD4 counts were created from the sample to account for disease progression, including a nonaffected control group) (Nichols et al., 2000).…”
mentioning
confidence: 99%